Hey there! :)
Answer:
(5, -2), or x = 5 and y = -2.
Step-by-step explanation:
We can solve the two equations algebraically by eliminating a variable:
2x + 5y = 0
3x - 4y = 23
Eliminate the x variable by finding the least common multiple and multiplying both equations:
3(2x + 5y = 0)
2(3x - 4y = 23)
Distribute and subtract the bottom equation from the top:
6x + 15y = 0
6x - 8y = 46
------------------
0x + 23y = -46
23y = -46
y = -2.
Plug in y into an equation to solve for x:
2x + 5(-2) = 0
2x - 10 = 0
2x = 10
x = 5. Therefore:
The solution to this equation is (5, -2), or x = 5 and y = -2.
The correct answer is: [B]: " y = 9 " .
_____________________________________________
Answer:
ye
Step-by-step explanation:
Answer:
-10x+7.5
Step-by-step explanation:
-2.5(4x-3)
Multiply each term by -2.5
-2.5 * 4x = -10x
-2.5 * 3 = 7.5
-10x + 7.5